Ventricular fibrillation in acute myocardial infarction: 20-year trends in the FAST-MI study. (28th October 2022) - Garcia, Rodrigue; Marijon, Eloi; Karam, Nicole; Narayanan, Kumar; Anselme, Frédéric; Césari, Olivier; Champ-Rigot, Laure; Manenti, Vladimir; Martins, Raphael; Puymirat, Etienne; Ferrières, Jean; Schiele, François; et al.
Abstract: Aims: Sudden cardiac arrest remains a major complication of acute myocardial infarction (AMI) and is frequently related to ventricular fibrillation (VF). Incidence and impact of VF among patients hospitalized for AMI were evaluated. Methods and results: Data from the FAST-MI programme consisting of 5 French nationwide prospective cohort studies between 1995 and 2015 were analysed, totally including 14 423 patients with AMI (66 ± 14 years, 72% males, 59% ST-elevation myocardial infarction). Overall, proportion of patients presenting in-hospital VF decreased from 3.9% in 1995 to 1.8% in 2015 ( P < 0.001). One-year mortality decreased from 60.7% to 24.6% ( P < 0.001). However, compared with patients who did not develop VF, the over-risk of 1-year mortality associated with VF was stable over time [hazard ratio (HR) 6.78, 95% confidence interval (CI) 5.03–9.14 in 1995 and HR 6.64, 95% CI 4.20–10.49 in 2015, P = 0.52]. This increased mortality in the VF group was mainly related to fatal events occurring prior to hospital discharge, representing 86.2% of 1-year mortality, despite the very low rate of implantable cardioverter defibrillator in the VF group (2.6%). Conclusion: This study demonstrates that in-hospital VF incidence and mortality in the setting of AMI have significantly decreased over the past 20 years. Nevertheless, VF remained steadily associated with approximately a 10-fold increased relative risk of in-hospital mortality, without an impact on post-discharge mortality. Beyond long-term cardiac defibrillation strategy, these results emphasize the need to identify in-hospital interventions to further reduce mortality in VF patients. Study registration: ClinicalTrials.gov Identifier: NCT00673036, NCT01237418, NCT02566200 Structured Graphical Abstract: Structured graphical abstract In-hospital ventricular fibrillation (VF) incidence and mortality in the setting of acute myocardial infarction have significantly decreased over the past 20 years. Nevertheless, VF remained steadily associated with a ∼10-fold increased relative risk of in-hospital mortality, without an impact on post-discharge mortality. FAST-MI, French registry of acute ST-elevation or non-ST-elevation myocardial infarction; PCI, percutaneous coronary intervention; VF, ventricular fibrillation.